2011
DOI: 10.2166/hydro.2011.089
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for processing raw LiDAR data to support urban flood modelling framework

Abstract: An assessment has been carried out to study the performance of seven different LiDAR filtering algorithms and to evaluate their suitability for urban flood modelling applications. It was found that none of these algorithms can be regarded as fully suitable to support such work in its present form. was observed between a model that uses a DTM modified by the progressive morphological filtering algorithm and the predictions of other models. The overall results suggest that incorporation of building basements wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…The coupled 1D/2D models are invaluable for this purpose. However, there is a great body of literature which suggests that great care is needed in the data collection and processing as well as the need to use an appropriate numerical modelling technique [8][9][10][11][12][13][14][15][16]. The DEM resolution used in the Ayutthaya work was 20x20 m. The model and maps produced were used for communication with local stakeholders and selection of remedial and flood protection works [3].…”
Section: Flood Mappingmentioning
confidence: 99%
“…The coupled 1D/2D models are invaluable for this purpose. However, there is a great body of literature which suggests that great care is needed in the data collection and processing as well as the need to use an appropriate numerical modelling technique [8][9][10][11][12][13][14][15][16]. The DEM resolution used in the Ayutthaya work was 20x20 m. The model and maps produced were used for communication with local stakeholders and selection of remedial and flood protection works [3].…”
Section: Flood Mappingmentioning
confidence: 99%
“…It is often the case that head losses, which can form around irregular geometry of urban features, are particularly difficult to model and take into account [19]. Such issues drive the need to use 1D and 2D modelling systems which have a good predictive capability in modelling floods in urban areas; see, for example, [29][30][31][32].…”
Section: Modelling Approachesmentioning
confidence: 99%
“…In addition to the issues related to DTM resolution, there are also issues associated with the efficacy of LiDAR filtering algorithms [31][32]. The work to date has shown that different filtering algorithms can produce different DTM data sets which in turn can cause different results from 2D models.…”
Section: Issues Concerning Filtering Algorithmsmentioning
confidence: 99%
“…Given the importance of temporal analysis, the use of one-and two-dimensional numerical hydrodynamic models has proved to be invaluable (e.g., [28][29][30]). However, there are numerous issues associated with data, models and mapping of results and so they require careful consideration (see, for example, [31][32][33][34][35][36][37][38][39][40][41][42]). …”
Section: The Notion Of Multifunctionalitymentioning
confidence: 99%